Development, validation, and verification of the gas chromatography-mas spectrometry method for detecting and quantifying major cannabinoids in the inflorescence of Cannabis sativa L - Saša D. Đurović; Nemanja Brkljača; Zorana Srećkov; Zorica Mrkonjić; Dejana Panković (Talanta Open)
Cannabis sativa L. is one the most intriguing plants these days. This is mainly because of the cannabinoids that are synthesized during maturation. Two main cannabinoids are cannabidiol (CBD) and Δ9-tetrahydrocannabinol (THC), followed by cannabigerol (CBG) and cannabinol (CBN). The CBD, THC, and CBN ratio determines whether it is the drug-type or fiber-type of the plant. We must have a precise and accurate sample preparation and analysis method to determine which it is. Several techniques are used for the analysis of cannabinoids. Among them is gas chromatography coupled with a flame ionization detector and/or mass spectrometer. To avoid the problem with elevated temperatures (decarboxylation, oxidation, and isomerization), decarboxylation was performed prior to the analysis, and tribenzylamine (TBA) was used as an internal standard. The first step was creating the calibration curves for CBD, THC, CBG, and CBN. After that, three hemp varieties (Helena, Marina, and Fedora 17) were used to validate and verify the method. High precision with intra-day and inter-day precisions (low coefficients of variation, CV) and accuracy for both standards and spiked samples proved the method's successful development, validation, and verification. The absence of CBN and Δ8-THC in plant samples showed that decarboxylation could be successfully applied, avoiding oxidation or isomerization of THC. Application of TBA showed that there is no need for deuterated standards. Quantitative analysis showed that analyzed strains are fiber-type plants and that the method developed in this study may be used to analyze cannabinoid content in plant samples accurately.